A Case Study Analysis of the Youth Guarantee Scheme Implementation in Italy (Lombardy Region). (November 2019) - Tsekoura, Maria
Using the implementation of the Youth Guarantee (YG) in the Italian context (Lombardy) as its point of departure, this article exemplifies the introduction of the YG scheme in national realities. Through review of relevant policy documents, the article identifies a contradiction between the policy model implied through the YG that builds upon a concept of active citizenship and an employment context that in reality offers limited structural opportunities for the enactment of these principles during processes of youth transition. This article will argue that initiatives for youth employment that are de-contextualized and lack a clear vision of youth lives can reinforce the existing order and power imbalances as they offer limited support for young people to develop a sense of success, self-determination and agency in terms of employability.